"Historical Concepts" And Related Concepts. (Eurasian Research Bulletin, 2024)
This scholarly article examines the field of historical issues and their profound significance in education in the field of editing. By examining the importance of historical judgment, grounded historical perspectives, and the interrelationship of editing across disciplines, this review seeks to develop critical thinking, cultural awareness, and the role of history in informed decision-making. By examining interrelated issues such as historiography, historical literacy, and historical empathy, this article comprehensively examines the multifaceted nature of historical knowledge and its educational significance.